2000
DOI: 10.1038/sj.ejhg.5200571
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum of the EPM2A gene in progressive myoclonus epilepsy of Lafora: high degree of allelic heterogeneity and prevalence of deletions

Abstract: Progressive myoclonus epilepsy of the Lafora type (Lafora disease) is an autosomal recessive disease characterised by epilepsy, myoclonus, progressive neurological deterioration and the presence of glycogen-like intracellular inclusion bodies (Lafora bodies). We recently cloned the major gene for Lafora disease (EPM2A) and characterised the corresponding product, a putative protein tyrosine phosphatase (LAFPTPase). Here we report the complete coding sequence of the EPM2A gene and the analysis of this gene in 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 13 publications
2
42
1
1
Order By: Relevance
“…1). It has been shown that the high prevalence of the R241X mutation is due to both a founder effect and recurrent events (Gomez-Garre et al 2000;Ganesh et al 2002a), perhaps explaining why LD is more common in the Mediterranean basin. Recurrent deletion mutations have also been reported for the EPM2A gene, accounting for up to 8% of total mutations ( Fig.…”
Section: Epm2amentioning
confidence: 99%
See 1 more Smart Citation
“…1). It has been shown that the high prevalence of the R241X mutation is due to both a founder effect and recurrent events (Gomez-Garre et al 2000;Ganesh et al 2002a), perhaps explaining why LD is more common in the Mediterranean basin. Recurrent deletion mutations have also been reported for the EPM2A gene, accounting for up to 8% of total mutations ( Fig.…”
Section: Epm2amentioning
confidence: 99%
“…1). Three deletion mutations with different deletion breakpoints have been identified in LD patients from Arabic, Jewish and Spanish populations (Minassian et al 1998;Serratosa et al 1999;Minassian et al 2000a, b;Gomez-Garre et al 2000;Ganesh et al 2002a). These deletions, which range in size from 30 to 80 kb, removed the first, second, or both first and second exons, of the EPM2A gene, thus creating a null allele.…”
Section: Epm2amentioning
confidence: 99%
“…Laforin also contains a functional polysaccharide binding domain [10][11][12] that binds preferentially to polyglucosan over glycogen [13]. Some forty mutations have been identified throughout all four exons of the EPM2A gene (http://projects.tcag.ca/lafora/) [9,12,[14][15][16][17]. Most mutations cause a loss of phosphatase activity in recombinant laforin [11,18].…”
mentioning
confidence: 99%
“…4,5 In spite of the remarkable allelic heterogeneity in the EPM2A gene, the R241stop mutation has been found in approximately 40% of Lafora disease patients with mutations in this gene. 6,7 The EPM2B gene (also called NHLRC1) encodes an E3 ubiquitin ligase (malin) and the most frequent mutation found is P69A. 8 Glycogen storage disease or glycogenosis type IV, also known as amylopectinosis or Andersen disease (MIN23250), is an autosomal recessive disorder caused by a deficiency of glycogen-branching enzyme (GBE) activity due to mutations in the GBE1 gene.…”
mentioning
confidence: 99%